The Employee’s Right to Reinstate in Case of Illegal Dismissal - Karapetyan, Mane (Bulletin of Yerevan University C: Jurisprudence, 2024)
This article presents the institution of exercising the right to reinstatement of an illegally dismissed employee and the problematic issues of its application in the context of balancing the reasonable interests of the employee and the employer. Reference was made to the cases when an illegally dismissed employee cannot be reinstated in his previous job due to objective circumstances, the existence of a relationship of trust between the employee and the employer was discussed, as well as the possibility of the employee’s reinstatement in his previous and equivalent job. Summing up the results of the study, we come to the conclusion that the legislator failed to regulate the institute of non-reinstatement of illegally dismissed employees to their previous jobs, giving the courts such wide discretion that in the same factual circumstances, irreconcilable judgments may be issued due to the judge’s subjective approach. In order to resolve the existing uncertainty we suggest to clarify the scope of discretion of the courts not to restore illegally dismissed employees to their former jobs, conditioned solely by objective factors. This article presents the experience of foreign countries, doctrinal approaches, international legal standards and judicial practice.